2008
DOI: 10.1111/j.1523-5378.2008.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Conventional, Regulatory, and Unconventional T Cells in the Immunologic Response to Helicobacter pylori

Abstract: Infection by the gastroduodenal pathogen Helicobacter pylori elicits a complex immunologic response in the mucosa involving neutrophils, plasma cells, eosinophils, and lymphocytes, of which T cells are the principal orchestrators of immunity. While so-called classical T cells (e.g. T-helper cells) that are activated by peptide fragments presented on antigen-presenting cells have received much attention in H. pylori infection, there exists a diverse array of other T cell populations that are potentially importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 196 publications
1
37
0
4
Order By: Relevance
“…In this study, we demonstrated that H. pylori triggered human gastric epithelial cells to produce TSLP, together with MIP-3␣ and BAFF. Because H. pylori products induce NF-B activation in gastric epithelial cells (8,27,41,47), H. pylori-induced NF-B activation in gastric epithelial cells may directly and/or indirectly upregulate the expression of TSLP, MIP-3␣, and BAFF in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that H. pylori triggered human gastric epithelial cells to produce TSLP, together with MIP-3␣ and BAFF. Because H. pylori products induce NF-B activation in gastric epithelial cells (8,27,41,47), H. pylori-induced NF-B activation in gastric epithelial cells may directly and/or indirectly upregulate the expression of TSLP, MIP-3␣, and BAFF in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Хотя H. pylori индуцирует гуморальный и клеточный иммунный ответ, он несовершенен и не позволяет элими-нировать этот микроорганизм [35]. Факторы вирулентности бактерии, такие как Vac A (vacuolating cytotoxin A), островок патогенности (cag PAI), белок теплового шока (heat shock protein, HSP 60), способны ингибировать Т-клеточную про-лиферацию и нарушать созревание дендритных клеток [36].…”
Section: а у т о и м м у н н ы е з а б о л е в а н и я и а с с о ц и unclassified
“…In contrast, the B-cell-defi cient μMT mice infected with H. felis exhibited severe pathological changes in the stomach such as mucosal hyperplasia and intestinal metaplasia, which was similar to the normalstate immune responses of C57BL/6 mice [ 27 ]. T cells plays the most important role in the immune responses to H. pylori infection [ 28 ], and the balance of Th1/Th2 immune responses are essential in the pathogenesis of H. pylori -associated disease and host defense mechanisms (Fig. 55.1 ).…”
Section: Differences In Individual Responsesmentioning
confidence: 99%